Strategic Objectives for Tourism Development in the Black Sea Basin - Iulian Adrian SORCARU (Dunarea de Jos University of Galati, 2021)
The fundamental objective of this paper was to determine the strategic objectives for sustainable tourism development in the countries of Black Sea Basin (Romania, Georgia, Bulgaria, Republic of Moldova), analyzing the perception of the tourists and residents. Another major objective was to identify the real involvement in tourism development of local and regional institutions, NGOs and enterprises from each state of the Black Sea Basin. The results presented in the paper are based on the answers of the five templates of questionnaires applied in Romania, Bulgaria, Georgia and Republic of Moldova and also on the research of the national legislation on tourism development in each country.